2021
DOI: 10.1097/scs.0000000000008444
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of Biodegradable Plates in Maxillofacial Fractures

Abstract: Background: Maxillofacial fractures require stable fixation for uneventful bony healing and optimal remodeling. Conventional titanium plates considered the gold standard of rigid internal fixation for many years, however due to the inherent drawbacks associated with metal devices biodegradable plates have been developed. Aim of the Study: To evaluate the efficacy of biodegradable plates as a treatment modality of rigid internal fixation for facial fractures and to assess the perioperative complications experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…One of the causes is the newly introduced abuse of motorcycles in the country, underaged drivers, and weak traffic safety laws for different vehicles like seat belts, helmets, and speed limits. This is identically in concordant with Hassan & Razzaq 11. and Bali et al,12 who found that most fractures happened due to road traffic accidents (60%).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…One of the causes is the newly introduced abuse of motorcycles in the country, underaged drivers, and weak traffic safety laws for different vehicles like seat belts, helmets, and speed limits. This is identically in concordant with Hassan & Razzaq 11. and Bali et al,12 who found that most fractures happened due to road traffic accidents (60%).…”
Section: Discussionsupporting
confidence: 88%
“…This is identically in concordant with Hassan & Razzaq. 11 and Bali et al, 12 who found that most fractures happened due to road traffic accidents (60%).…”
Section: Resultsmentioning
confidence: 97%
“…[21][22][23] Biodegradable plates and screws have been available since the 1990s though titanium remains far more common for most applications outside pediatric craniofacial surgery. 24 Regarding hardware design, a wide variety of plating systems have been developed for diverse applications throughout the face and skull. Miniplates and microplates offer low-profile options for rigid internal fixation.…”
mentioning
confidence: 99%
“…Then, in 1983, Branemark reported the benefits of titanium hardware (ie, biocompatibility, resistance to corrosion, high strength-to-weight ratio), and titanium was quickly accepted as the standard for craniofacial hardware 21–23 . Biodegradable plates and screws have been available since the 1990s though titanium remains far more common for most applications outside pediatric craniofacial surgery 24 . Regarding hardware design, a wide variety of plating systems have been developed for diverse applications throughout the face and skull.…”
mentioning
confidence: 99%